جاهزية البيئة المحاسبية في الجزائر لتطبيق محاسبة القيمة العادلة من وجهة نظر أكاديمي وممارسي مهنة المحاسبة دراسة حالة - حسين معايطية; شعيب طيار (My University, 2022)
This study aims to know the extent of the readiness of the Algerian accounting environment to apply the Fair value of a survey of a sample of academics and practitioners of the accounting profession, namely: accountancy experts, account keepers, in addition to accountants in economic institutions. Processable forms 40 forms. Through the outputs of the spss program, the study demonstrated the existence of a strong relationship between the accounting environment and fair value, and there is an impact on the readiness of the Algerian accounting environment to apply value from the point of view of an academic and accountancy practitioners Finally, the study recommends, in light of the acceleration of economic transformations and the development and openness of international financial markets, the necessity of promoting the Algerian business environment with its various components and making it stimulating and helpful for the application of international accounting standards, especially fair value, in addition to updating the financial accounting system, according to what is amended and issued by international accounting standards ...................................................... تهدف هذه الدراسة إلى معرفة مدى جاهزية البيئة المحاسبية الجزائرية لتطبيق القيمة العادلة، من خلال إستقصاءعيينة من الأكاديميين وممارسي مهنة المحاسبة وهم: الخبراء المحاسبين، محافظي الحسابات، بالإضافة إلى المحاسبين في مؤسسات الاقتصادية ولتحقيق أهداف الدراسة تم الاعتماد على تقنيات البحث الكمي عن طريق أداة الإستبيا ن، حيث بلغ عدد الاستمارات القابلة للمعالجة 40 استمارة . من خلال مخرجات برنامج spss أثبتت دراسة وجود علاقة قوية بين البيئة المحاسبية والقيمة العادلة ويجد هناك أثر حول جاهزية البيئة المحاسبية الجزائرية لتطبيق القيمة العادلة من وجهة نظر أكاديمي وممارسي مهنة المحاسبة وفي الأخير توصي الدراسة وفي ظل تسارع التحولات الإقتصادية وتطور وانفتاح الأس واق المالية الدولية بضرو رة النهوض ببيئة الأعمال الجزائرية بمختلف مكوناتها وجعلها محفزة ومساعدة لتطبيق المعايير المحاسبية الدولية وخاصة القيمة العادلة بالإضافة إلى تحيين النظام المحاسبي المالي، وفق ما يعدل وما يصدر من معايير محاسبية دولية .